Optimum relative concentrations of phosphorus and sulfur in coffee fertilization in a Dark-Red Latosol, at Machado, MG, Brazil - Venegas, Victor Hugo Alvarez; Guimarães, Paulo Tácito G.; Freire, Francisco M. (Pesquisa Agropecuaria Brasileira, 2014)
To study the P - S equilibria in coffee (Coffea arabica L.) fertilization (Catuai cultivar) in a Dark-Red Latosol, "cerrado" phase, at Machado, MG, Brazil, a field experiment was carried out with the treatments selected according to "Richard’s cut method". The cut values (0.8, 0.4 and 0.2) were defined as a function of the soil P and S maximum adsorptions. In each cut, four equilibria were studied. The sources of P and S were concentrated superphosphate and gypsum. The treatment effects were evaluated in the second and third years after planting. The plant height and the stem and top diameter, in the second year after planting showed the application of S as necessary only in the presence of high levels of P (cut 0.8). In the yielding phase (third year after planting) the results showed that for the low levels of P applied the soil S was enough. On the other hand, for high levels of P (cuts 0.4 and 0.8), the application of both P and S was necessary. Considering yield, for the cut 0.4, the optimum equilibrium was observed with the applications of 70 g P2O5 of and 4 g of S per planting hole, and for the cut 0.8, with 135 and 9 g, respectively. The results indicate that P is more required than S during the growth phase of coffee. With the plant growth and with the increase in the rate of P applied per plant, the S requirement becomes more important.